2008
DOI: 10.1021/cm701966c
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Wormhole and Ordered Mesostructures and Their Applicability as Optically Ion-Sensitive Probe Templates

Abstract: Large-scale cubic Pm3n silica monoliths (HOM) were fabricated in wormhole and ordered mesostructures and in shape- and size-controlled cage pores by using a simple and fast strategy. The functional use of these 3D HOM monoliths as probe anchoring templates enabled the efficient designs of optical nanosensors. In this regard, the synthesized chromoionophore was physisorbed into the 3D HOM pore surface carriers without potential leaching. Results revealed that the structural features of the HOM monoliths such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 126 publications
1
50
0
Order By: Relevance
“…These results indicated that the behavior of azo-probe solid strip with the Co(II) analyte and its matrix environments showed conspicuous divergence from their solution chemistry. Such finding might indicate that the orientation and arrangement of the probe molecular assemblies mounted onto HOM-2 solid carriers with open-pore arrays, high surface areas, and high pore volumes allowed stable thermodynamic binding of Co(II)-probe chelates (El-Safty et al 2008a, 2008b, 2008c.…”
Section: Hexagonal Ion Selective Sensor Stripsmentioning
confidence: 98%
See 4 more Smart Citations
“…These results indicated that the behavior of azo-probe solid strip with the Co(II) analyte and its matrix environments showed conspicuous divergence from their solution chemistry. Such finding might indicate that the orientation and arrangement of the probe molecular assemblies mounted onto HOM-2 solid carriers with open-pore arrays, high surface areas, and high pore volumes allowed stable thermodynamic binding of Co(II)-probe chelates (El-Safty et al 2008a, 2008b, 2008c.…”
Section: Hexagonal Ion Selective Sensor Stripsmentioning
confidence: 98%
“…7A) (Nicole et al 2004). The color intensity and homogeneity increased with increasing Co(II) ion concentration (El-Safty et al 2008a, 2008b, 2008c. The colorimetric quantification of hexagonal strip for Co(II) ion-sensing over a wide range of concentration was also investigated by monitoring the UV/Vis reflectance spectra.…”
Section: Optical Ion-sensing Monolithic Stripsmentioning
confidence: 99%
See 3 more Smart Citations